Antiosteoporosis effect of geraniin on ovariectomy‐induced osteoporosis in experimental rats. Issue 6 (23rd March 2021) - Wang, Xiuhui; Wang, Minghui; Cui, Xu; Li, Zhuokai; Guo, Shengyang; Gao, Feng; Ma, Ming; Wang, Zhe
Abstract: Osteoporosis is a skeletal condition that is characterized by decreasing bone density and deteriorating bone mass. The plant‐based phytoconstituent such as geraniin possesses better therapeutic potentials in biomedical field. In the current experimental study, we planned to scrutinize the therapeutic potential of geraniin against ovariectomy (OVX)‐induced osteoporosis in rats and find the possible mechanism. Healthy Sprague Dawley rats were randomized into six groups and subjected to geraniin and alendronate (ALN) treatment for 10 weeks. Body weight, uterus, femur weight, bone biochemical, bone turnover markers, inflammatory cytokine, calcium, phosphorus, vitamin D (Vit D), urine, hormones, and antioxidant level were estimated. Geraniin significantly ( p < .001) reduced the level of bone turnover markers including beta‐CrossLaps (β‐CTx), ALN, osteocalcin (OC), alkaline phosphatase (ALP), and bone Gla protein (BGP); reduced the biomechanical parameters including maximum load, energy, stiffness, maximum stress, and Young's modulus; reduced the level of calcium (Ca) and phosphorus (P); and increased the level of vitamin D (Vit D) as compared with OVX‐induced osteoporosis rats. Geraniin increased the level of bone structure parameters, namely bone mineral density, bone mineral content, tissue mineral density, bone volume fraction, and trabecular number; increased the level of osteoprotegerin (OPG) and OPG/RANKL; and reduced the level of receptor activator of nuclear factor kappa‐Β ligand (RANKL). Geraniin significantly ( p < .001) increased the level of glutathione (GSH) and reduced the level of malonaldehyde (MDA) in the liver, intestine, and bone of OVX‐induced osteoporosis rats. Geraniin significantly ( p < .001) decreased the level of tumor necrosis factor‐α (TNF‐α), interleukin‐1β (IL‐1β), and interleukin‐6 (IL‐6) pro‐inflammatory cytokines. We also argue that geraniin could be an excellent candidate to treat and control bone‐related disease or disorders.